Risk Factors of Postpartum Depression at Dr. Moewardi Hospital, Surakarta - Ria, Matilda Bupu; Budihastuti, Uki Retno; Sudiyanto, Aris (Journal of Maternal and Child Health, 2018)
Background: Postpartum depression is one of the emotional disturbances that results from failure to postpartum psychological adaptation process. The global prevalence of postpartum depression is 10-15%. This study aimed to analyze the risk factors of pregnancy on the incidence of postpartum depression.Subjects and Method: This was an analytic and observational study with a cross-sectional design. The study was conducted at Dr. Moewardi hospital, from December 2017 to January 2018. A total sample of 150 postpartum mothers was selected for this study by exhaustive sampling. The dependent variable was postpartum depression (PPD). The independent variables were maternal age, stress, parity, unwanted pregnancy, type of labor, family income, family support, and domestic violence. The data were collected by questionnaire and analyzed by path analysis model.Results: Postpartum depression was directly and positively affected by psychological stress (b= 2.15; 95% CI= 1.17 to 3.13; p<0.001), delivery type (b= 1.27; 95% CI= 0.32 to 2.21; p= 0.008), and unwanted pregnancy (b= 1.57; 95% CI= 0.57 to 2.58; p= 0.002). Postpartum depression was directly but negatively affected by family income (b= -1.52; 95% CI= -2.51 to -0.54; p= 0.002), parity (b= -1.24; 95% CI= -2.21 to -0.28; p= 0.011), and family support (b= -1.31; 95% CI= -3.28 to -0.24; p= 0.016). Psychological stress increased with domestic violence (b= 2.68; 95% CI= 0.64 to 4.73; p= 0.010) and decreased with maternal age (b= -0.91; 95% CI= -1.68 to -0.13; p= 0.022). Parity increased with maternal age (b= 1.66; 95% CI= 0.79 to 2.53; p<0.001). Domestic violence decreased with maternal age (b= -1.34; 95% CI= -2.85 to 0.16; p= 0.081).Conslusion: Psychological stress, delivery type, unwanted pregnancy, family income, parity, and family support, are direct risk factors for postpartum depression.Keywords: Postpartum depression, unwanted pregnancy, domestic violence, family supportCorrespondence: Matilda Bupu Ria. Masters Program in Public Health, Universitas Sebelas Maret, Surakarta,  Jl. Ir. Sutami No. 36 A, 57126, Surakarta, Jawa Tengah. E-mail: matildabupuria19@gmail.com. Mobile +6281241254153.Journal of Maternal and Child Health (2018), 3(1): 81-90https://doi.org/10.26911/thejmch.2018.03.01.08